2009
DOI: 10.1007/s00441-008-0733-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sur1 gene inactivation on the morphology of mouse pancreatic endocrine tissue

Abstract: In congenital hyperinsulinism of infancy (CHI), the loss of K-ATP channels (composed of Kir6.2 and SUR1 subunits) in beta cells induces permanent insulin secretion and severe hypoglycaemia. By contrast, Sur1 ( -/- ) mice do not present such defects. We have investigated the impact of Sur1 gene inactivation on mouse islet cell morphology, structure and basic physiology. Pancreata were collected from young, adult and old wild-type (WT) and Sur1 ( -/- ) mice. After immunostaining for hormone, the total endocrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…The distribution of α-cells can be very different in some transgenic mice. For instance, α-cells are frequently located in central regions of islets in K ATPdeficient mouse models, such as SUR1 (Marhfour et al 2009) or Kir6.2 knockout mice (Seino et al 2000;Winarto et al 2001) or in mice completely or partially deficient in specific adhesion molecule (Esni et al 1999). The reasons for this altered distribution are unknown.…”
Section: Microanatomy Of the Islets Of Langerhansmentioning
confidence: 96%
“…The distribution of α-cells can be very different in some transgenic mice. For instance, α-cells are frequently located in central regions of islets in K ATPdeficient mouse models, such as SUR1 (Marhfour et al 2009) or Kir6.2 knockout mice (Seino et al 2000;Winarto et al 2001) or in mice completely or partially deficient in specific adhesion molecule (Esni et al 1999). The reasons for this altered distribution are unknown.…”
Section: Microanatomy Of the Islets Of Langerhansmentioning
confidence: 96%
“…It has been demonstrated that, despite the total absence of functional K ATP channels, islet β-cells from Kir6.2 -/-and Sur1 -/-mice do not hyper-secrete insulin in vivo (Miki et al 1998;Seghers et al 2000;Nenquin et al 2004;Szollosi et al 2007); however, β-cells from CHI infants hyper-secrete insulin even in the presence of hypoglycaemia (Aynsley-Green et al 1981;Dunne et al 2004). Accordingly, whereas Sur1 -/-β-cells have apparently normal nuclear and cell surface morphology and the same number of insulin granules and proinsulin mRNA levels as WT islets (Marhfour et al 2009;present study), β-cells from CHI infants display many alterations characteristic of hyper-functioning β-cells such as abnormally large nuclei, abundant cytoplasm, greater cell size, high proinsulin (in the Golgi area) and low insulin content (Rahier et al 1984(Rahier et al , 2000Sempoux et al 1998Sempoux et al , 2003.…”
Section: Discussionmentioning
confidence: 84%
“…Cytoplasmic Kir6.2 staining intensity was similar in both WT and Sur1 -/-islets. Ultrastructure of endocrine cells Despite their abnormal distribution in Sur1 -/-islets (Marhfour et al 2009), endocrine cells were easily identified by the ultrastructural characteristics of their hormone-containing granules in both types of mice (insulin-containing granules, Fig. 3a-b; glucagon-containing granules, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations